2017
DOI: 10.3390/rs9030257
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Rice Fields in Urban Shanghai, Southeast China, Using Sentinel-1A and Landsat 8 Datasets

Abstract: Sentinel-1A and Landsat 8 images have been combined in this study to map rice fields in urban Shanghai, southeast China, during the 2015 growing season. Rice grown in paddies in this area is characterized by wide inter-field variability in addition to being fragmented by other land-uses. Improving rice classification accuracy requires the use of multi-source and multi-temporal high resolution data for operational purposes. In this regard, we first exploited the temporal backscatter of rice fields and backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 49 publications
3
49
0
3
Order By: Relevance
“…The Landsat 8 OLI consists of eight multispectral bands (30 m), one panchromatic band (15 m), and two thermal bands (100 m). We assembled clear (0-5% cloud cover) Landsat 8 OLI images covering the study area in 2015 (including two adjacent overlapping Landsat footprints, path/row: 123/40 and 123/41) for the experiment (https://www.usgs.gov/) [49]. Radiometric calibration was performed to convert the digital number (DN) value to surface spectral reflectance, and atmospheric correction was conducted by using the FLAASH model of ENVI, version 5.1 [49].…”
Section: Landsat 8 Oli Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The Landsat 8 OLI consists of eight multispectral bands (30 m), one panchromatic band (15 m), and two thermal bands (100 m). We assembled clear (0-5% cloud cover) Landsat 8 OLI images covering the study area in 2015 (including two adjacent overlapping Landsat footprints, path/row: 123/40 and 123/41) for the experiment (https://www.usgs.gov/) [49]. Radiometric calibration was performed to convert the digital number (DN) value to surface spectral reflectance, and atmospheric correction was conducted by using the FLAASH model of ENVI, version 5.1 [49].…”
Section: Landsat 8 Oli Datamentioning
confidence: 99%
“…We assembled clear (0-5% cloud cover) Landsat 8 OLI images covering the study area in 2015 (including two adjacent overlapping Landsat footprints, path/row: 123/40 and 123/41) for the experiment (https://www.usgs.gov/) [49]. Radiometric calibration was performed to convert the digital number (DN) value to surface spectral reflectance, and atmospheric correction was conducted by using the FLAASH model of ENVI, version 5.1 [49]. The NDVI was computed by band 4 (red) and band 5 (NIR) using the surface spectral reflectance images [50,51].…”
Section: Landsat 8 Oli Datamentioning
confidence: 99%
“…The Sentinel-1 A and Sentinel-1B satellites are carrying C-band SAR sensors providing imagery in single (VV or HH) and dual polarisations (VV + VH or HH + HV) with high temporal resolutions (12 days to 6 days in regions towards the poles) and with a long-term monitoring possibility (European Space Agency (ESA, 2013). To our knowledge, only a few studies have used Sentinel-1 time-series data for rice crop mapping (Chen et al, 2016;Nguyen et al, 2016;Mansaray et al, 2017;Nguyen and Wagner, 2017;Torbick et al, 2017;Clauss et al, 2018) and none of them has applied Sentinel-1 for the detection of rice crop establishment methods. Given that most rice crop mapping algorithms depend on the detection of a strong water signal at the start of the growing season, which is typical of TP rice but not of DS rice, a more comprehensive understanding of the observable differences due to TP and DS would also improve the capability of rice mapping systems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Blaes et al [20] reported a 5% increase in accuracy by adding ERS and RADARSAT imagery with optical SPOT and Landsat images. Lamin R. Mansaray et al [21] successfully used five Sentinel 1A and one Landsat-8 images for paddy rice field mapping in urban Shanghai and reported a 5% increase in overall accuracy than individuals. Rosenthal and Blanchard [22] and Brisco et al [23] also reported that the combination of optical and radar datasets in crop mapping increased the overall accuracy by 20% and 25%, respectively.…”
mentioning
confidence: 99%